Functionalization of Cellulose through Polyurethanization by the Addition of Polyethylene Glycol and Diisocyanate - Imam Prabowo; Ghiska Ramahdita; Mochamad Chalid (Indonesian Journal of Chemistry, 2019)
Plastic consumption becomes a main factor of land pollution due to poor degradability. To reduce the impact of land pollution, a biodegradable material such as cellulose, which has biodegradability, high strength, and specific modulus, is combined with plastic materials. However, the combination result poor compatibility because of different properties. Through grafting technique, the compatibility can be improved. The experimental results were conducted using Fourier-Transform Infrared (FT-IR), Simultaneous Thermal Analysis (STA), Scanning Electron Microscope (SEM) and 1H-Nuclear Magnetic Resonance (1H-NMR). The results revealed that the structure of hybrid material consists of cellulose as a chain extender in a hard segment which connects two diisocyanate compounds and polyol as a soft segment. The addition of 2.5 g of cellulose and 5 mole of diisocyanate can increase the melting temperature (Tm) of the hard segment from 417.92 to 460.72 °C and from 417.92 to 467.04 °C respectively. However, its melting temperatures of soft segment decrease from 378.53 to 350.74 °C and from 378.53 to 350.74 °C as well as the glass transition temperature (Tg) of the soft segment from 73.7 to 57.2 °C and from 73.7 to 71.8 °C. This study also discovers that cellulose and diisocyanate can raise thermal stability and create good interfacial bonding.